The clinician manager in rural Western Australia: a sensemaking perspective of the role - Lewis, Janice A. (Curtin University, 2001)
Economic, political and social forces are driving the implementation of reforms in health service systems worldwide. As the health industry concentrates on ways to improve operations and to achieve overall cost effectiveness, health service organisations are developing and implementing structural changes to address issues of cost containment, utilisation and resource allocation. One approach has been to devolve resource allocation and utilisation decisions to the program or unit level. Clinical practitioners have been required to assume general management responsibilities in addition to their clinical role. A new type of clinician, the clinician manager has emerged to take on this task. Despite the trend towards the clinician manager role in many sections of health care world wide, there is little research in the area and a poor understanding of the experience of the role.The aim of this research was to explore clinician managers' perceptions of their experiences in their adaptation to and their enactment of the new role. The study was based in the symbolic interactionist paradigm. Sensemaking, the process by which individuals ascribe meaning to the events in their environment, provided a theoretical context that directed the inquiry. Grounded theory was the methodological approach. The research sample was made up of Directors of Nursing/Health Service Managers, a clinician manager role that had emerged from the restructuring of rural health services in Western Australia. Data was gathered from in-depth interviews.Findings suggested that sensemaking was influenced by structural and personal elements. Structural elements were created by the stakeholders, individuals and groups who relied on the clinician manager for the achievement of their goals but upon whom, in turn, the clinician manager relied upon for their support and cooperation. The sensemaking process of the clinician manager was mediated by the interaction with the stakeholders - the most influential factors being the clinician manager's perceptions of the trustworthiness of the stakeholders, the political behaviour that characterised the interactions with the stakeholder and role stress. In particular, role conflict, role ambiguity and role overload emerged. Personal elements were the personal characteristics of the clinician manager - the most salient being the experience of role strain, self-efficacy (i.e. their belief in their ability to do the job) and their commitment to the sensemaking process.Circumstances in the environment constrained their reliance on others for validation of their explanations of events and the actions they took. Most made decisions based on intuition and "gut feeling" - validating these decisions with subjective evaluations of outcomes and retrospective explanations. These processes were further mediated by the characteristics of the individual, particularly perceptions of self-efficacy. The ways in which the clinician managers adapted to and interpreted their role was diverse, which made the role more an expression of individual preferences than a coherent part of a larger organisational structure. Findings indicated that the clinician managers relied on their sensemaking processes in order to explain the ambiguous nature of their practice environment and to plan actions within the context of a role that was poorly defined by the organisation.